Phenolic composition and antioxidant properties of ex-situ conserved tomato (Solanum lycopersicum L.) germplasm. (November 2019) - Pinela, José; Montoya, César; Carvalho, Ana Maria; Martins, Valter; Rocha, Filomena; Barata, Ana Maria; Barros, Lillian; Ferreira, Isabel C.F.R.
Abstract: Tomato ( Solanum lycopersicum L.) local varieties represent a reservoir of genetic diversity for desirable quality traits. In this study, a representative collection of table tomato germplasm conserved ex-situ in the Portuguese Gene Bank was characterized for its polyphenols composition and antioxidant capacity. Phenolic acids, such as caffeic and p -coumaric acids bounded to a hexose and 5- O -caffeoylquinic acid, corresponded to 71–98% of the identified phenolic compounds; while the remaining fraction consisted of quercetin and kaempferol glycoside derivatives. Among the studied tomato accessions, it was possible to identify those that stand out for the analysed bioactive traits. These findings highlighted the interest of using Portuguese tomato germplasm in breeding programs or of reintroducing into cultivation these local varieties used for fresh consumption. Graphical abstract: Unlabelled Image Highlights: Ex-situ conserved table tomato germplasm was analysed for bioactive quality traits. Phenolic acids corresponded to 71–98% of the total identified phenolic compounds. The remaining fraction consisted of quercetin and kaempferol glycoside derivatives. Promising tomato germplasm to be used in breeding programmes was identified. Portuguese tomato accessions have potential to be reintroduced into cultivation.